PENGARUH KEPRIBADIAN INTROVERT DAN EKSTROVERT TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP IT PUTRI AL-IHSAN WAHDAH KABUPATEN BANTAENG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of introverted and extroverted personalities on students’ academic achievement in Islamic Religious Education at SMP IT Putri Al-Ihsan Wahdah Islamiyah in Bantaeng Regency. This study employs a quantitative approach using an ex post facto method. The study population consists of 60 students, all of whom were selected as the sample using a saturated sampling technique. Data collection techniques included questionnaires and documentation, while data analysis utilized multiple linear regression with the assistance of SPSS software. The results of the study indicate that: (1) an introverted personality has a positive and significant effect on academic achievement, with a calculated t-value of 3.024 > the critical t-value of 1.296 and a significance level of 0.004 < 0.05, as well as a regression coefficient of 0.435; (2) extroverted personality has a positive and significant effect on academic achievement with a calculated t-value of 2.533 > the critical t-value of 1.296 and a significance level of 0.001 < 0.05, as well as a regression coefficient of 0.376; (3) Simultaneously, introverted and extroverted personalities have a significant effect on academic achievement, with a calculated F-value of 17.669 > the critical F-value of 3.16 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.383 indicates that 38% of academic achievement is influenced by introverted and extroverted personality traits, while the remaining 62% is influenced by other factors outside the scope of this study.